Effect of Ns Gene Dosage and Temperature on the Level of Potato Resistance to PVS - Beata Tatarowska; Dorota Milczarek; Katarzyna Szajko; Jarosław Plich; Dominika Boguszewska-Mańkowska (Agriculture, 2025)
The aim of this study was to verify the influence of the dosage of the gene Ns (simplex or duplex), derived from S. tuberosum subsp. Andigena, on potato resistance to PVS and to evaluate changes in the response of potatoes depending on the method of inoculation used and different cultivation temperatures. The analyses carried out made it possible to distinguish 42 clones in duplex and 8 in simplex form. The analysis showed that the Ns gene, even in simplex form, confers full resistance to PVS. Our results also suggest that an increase in temperature may weaken the resistance response of host plants carrying the Ns gene. In our research, PVS overcame the resistance conferred by the Ns gene at higher temperatures in three tetraploid clones: Ns-II-3, Ns-II-4 and Ns-II-81. These clones were classified as ‘temperature-dependent’ (TD). For clones Ns-II-6, Ns-II-10, Ns-II-40 and Ns-II-43, the increase in temperature had no effect on the resistance response of host plants carrying the Ns gene. These clones were classified as ‘resistant’ (R).